PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS CONTEXTUAL TEACHING LEARNING MATERI INTEGRAL TAK TENTU FUNGSI ALJABAR - Hulu, Alfin Jones (Universitas Nias Raya, 2024)
This research aims to develop a Student Worksheet based on Contextual Teaching and Learning on social arithmetic material that is valid, practical and effective. The type of research used in this research is research and development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The data collection techniques used were validation sheets, student response questionnaires, and student learning outcomes tests. Meanwhile, the data analysis technique used is qualitative and quantitative data analysis. Based on research and discussion, the validation results from material experts are 83.33% with very feasible criteria, the validation results from media expert validators are 80% with very feasible criteria, and the validation results from language expert validators are 92% with very feasible criteria. The practicality test results of individual trial respondents were 73.66% with interesting and practical criteria, the results of small group trial respondents were 75.50% with the interesting and practical category, and the results of field trial respondents were 75.54% with interesting and practical categories. practical. The effectiveness results obtained an average value of 81% in the very effective category. Researchers hope that this LKPD can be used to improve students' abilities in the material of indefinite integrals in algebraic functions.